Assessment of neuroimaging techniques as biomarkers of the progression of Parkinson's disease - Brooks, D.J; Frey, K.A; Marek, K.L; Oakes, D; Paty, D; Prentice, R; Shults, C.W; Stoessl, A.J (Experimental neurology, 2003)
A major goal of research in Parkinson's disease (PD) has been the development of treatments to slow the progressive degeneration of the nigrostriatal dopaminergic system and to reduce the functional decline of patients. Because of the uncertainty in the ability of the clinical evaluation to reflect the status of the nigrostriatal dopaminergic system once dopaminergic therapy has commenced, investigators in PD have sought to develop alternative measures of disease. One approach, which has been extensively explored, is neuroimaging with radiotracers that interact with processes central to dopaminergic neurotransmission in the nigrostriatal dopaminergic axons—conversion of levodopa to dopamine through aromatic amino acid decarboxylase (AADC), [ 18F]fluorodopa PET, storage of dopamine in synaptic vesicles via the vesicular monoamine transporter 2 (VMAT2), (+)-[ 11C]dihydrotetrabenazine PET, and reuptake of dopamine into axons via the dopamine transporter (DAT), [ 123I]β-CIT SPECT, and a number of other PET and SPECT ligands. During the 54 th Annual Meeting of the American Academy of Neurology, a group of investigators active in the fields of biomakers, neuroimaging, and neuroprotection met to review the three techniques mentioned above. Prior to the meeting, the participants developed consensus on a set of 10 criteria for a neuroimaging technique to be considered adequate as a biomarker for progression of PD and levels at which the available data for each technique indicate that the criterion was met. The criteria and each of the three imaging techniques mentioned above were reviewed, and the results of that meeting are presented.